Empowering Women through Mansiro Weaving in Nagari Canduang Koto Laweh - Sarifatul Aini; Setiawati Setiawati (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2023)
The existence of a potential regional community empowerment program that can increase income and community independence, namely the Mansiro woven activity, motivates this research. The goal of this research was to gain a better understanding of the stages and processes of community empowerment through woven mansiro in Nagari Canduang Koto Laweh. This is a qualitative study that employs a case study approach. The research subjects were community members who were members of the mansiro woven group, and the research informants were managers, nagari officials, PKK, and local residents. Interviews, observation, and documentation were used to collect data. The data analysis techniques employed, namely data reduction, data presentation, and conclusion drawing. The source and method triangulation technique is used to validate data. According to the findings of this study: (1) Empowerment of women through woven mansiro in Nagari Canduang Koto Laweh is seen from the aspect of awareness by motivating the community and educating the community so that the community wants to take action. (2) The empowerment of women through woven mansiro in Nagari Canduang Koto Laweh seen from the aspect of knowledge transformation is carried out by providing training, coaching and assistance to the community. (3) The empowerment of women through woven mansiro in Nagari Canduang Koto Laweh is seen from the aspect of increasing community skills, namely that the community has succeeded in forming an independence. Keywords: Empowerment process, woven Mansiro